The extraction of papain from papaya leaves - Nur Dianaty, Nordin (2010)
The use of papaya leaves to extract papain enzyme was evaluated for different extraction technique mainly using grinding method, enzyme-assisted extraction and ultrasonication. Enzyme concentration was then determined by measuring the amount of amino acid released in the reaction of protease assay. The combination of grinding method, enzyme-assisted extraction was proven to give highest yield of papain by 36.75% when compared to grinding alone. Then further purification of the extracted papain was done by using ammonium sulfate precipitation. The optimized concentration of ammonium sulfate saturation was achieved at 55% concentration in order to fully precipitate the protein. The combination of grinding, enzyme-assisted extraction and ultrasonication can be considered as a potential extraction technique to extract papain as it is more delicate towards protein extraction. Furthermore, the investigation on other source of papain such as from the petioles, stalks and stem could also be done.